Experimental Investigation on Thermal Conduction of Carbon Nanotubes Reinforced Copper Matrix Composites - ., Faiz Ahmad, Muhammad Aslam, M Rafi Raza, Ali S Muhsan (2014)
he performance of the micro-chip is affected by overheating and hence reduces the efficiency of electronic devices. The development of high thermal conductivity material can solve problems associated with dissipation of heat from the micro-chips. Thermal conductivity for carbon nanotubes (CNTs) are in the ranges of 1200-3000 W/moK which considered as the best candidate material for heat sink applications. This research investigates the fabrication of CNTs reinforced copper composites using powder metallurgy method. Copper powder and CNTs were ball milled to prepare mixtures and compacted at 600 MPa to fabricate test samples. The compacted test samples were sintered in argon atmosphere at 850oC. Sintered density of CNTs/Cu composites was measured and compared with theoretical density.